On Effective Locations of Catalytic Active Sites in Phase Boundary Catalysts - Hadi Nur; Nur Hidayah Mohd Ran; Nursyafreena Attan; Shigeru Ikeda; Bunsho Ohtani (Journal of Mathematical and Fundamental Sciences, 2012)
Zeolite loaded with alkylsilane-covered titanium oxide was found to be more effective than its nonporous silica counterpart as phase-boundary catalyst (PBC) to promote epoxidation of alkenes with aqueous hydrogen peroxide. It was demonstrated that the phase-boundary catalyst system required neither stirring to make an emulsion, nor addition of a cosolvent to make a homogeneous solution to drive the reaction. However, some basic facts about them remain unclear, such as the question as to where an effective location of the active sites of PBC resides: is it on the external surface of the catalysts, or in their pores? In order to elucidate this problem, TS-1, HZSM-5 and zeolite loaded with alkylsilane"“covered sulfonic acid in which the location of the active sites is mainly inside the pore system, were chosen as model catalysts. Catalytic activities of the catalysts TS-1 and HZSM-5 were examined after modification with n-octadecyltrichlorosilane (ODS). Their activities were compared with zeolite loaded with alkysilane-covered titanium oxide particles, in which the active sites are on the external surface in reactions of 1-octene with aqueous H2O2 and cyclohexene with water as model reactions. The study suggests that the location of the active sites on the external surface plays an important role in the phenomenon of phase-boundary catalysis.